Screening and Biological Activity of Indigenous Plant Extracts against Pulse Beetle, Callosobruchus Chinensis (Bruchidae: Coleoptera) - Ahad, Md. Abdul; Haque, Md Fazlul; Akter, Mst. Mottakina; Islam, Md Najrul; Rahman, Sheikh Arafatur (International Journal of Bio-resource and Stress Management, 2012)
The experiments were conducted in the laboratory of Department of Entomology, Hajee Mohammad Danesh Science and Technology University, Dinajpur, during June 2009 to June 2010. N-hexane solvent extracts of 13 local plants were tested for screening of their insecticidal activity against pulse beetle, Callosobruchus chinensis L. All plants extracts were showed insecticidal activity by affecting through mortality, inhibition of F1 adult emergence, reduced seed damage and fecundity or acting repellency. Emblica officinalis and Annona reticulata extracts were showed 100% mortality within 72 hours. Nerium oleander showed 90% and 96.67% mortality in 2%, and 3%, respectively. Annona reticulata and Polygonum hydropiper extract reduced the seed damage 2% and 9.33% at 0.5% to 3%, respectively. Annona reticulata and Polygonum hydropiper also reduced the fecundity of pulse beetle. Repellency class varies II to IV; but Polygonum hydropiper showed significant results following by Lantana camara.